A Race-neutral Approach to the Interpretation of Lung Function Measurements - Bowerman, Cole; Bhakta, Nirav R; Brazzale, Danny; Cooper, Brendan R; Cooper, Julie; Gochicoa-Rangel, Laura; Haynes, Jeffrey; Kaminsky, David A; Lan, Le Thi Tuyet; Masekela, Refiloe; McCormack, Meredith C; Steenbruggen, Irene; et al. (American journal of respiratory and critical care medicine, 2023)
The use of self-reported race and ethnicity to interpret lung function measurements has historically assumed that the observed differences in lung function between racial and ethnic groups were because of thoracic cavity size differences relative to standing height. Very few studies have considered the influence of environmental and social determinants on pulmonary function. Consequently, the use of race and ethnicity-specific reference equations may further marginalize disadvantaged populations. To develop a race-neutral reference equation for spirometry interpretation. National Health and Nutrition Examination Survey (NHANES) III data ( = 6,984) were reanalyzed with sitting height and the Cormic index to investigate whether body proportions were better predictors of lung function than race and ethnicity. Furthermore, the original GLI (Global Lung Function Initiative) data ( = 74,185) were reanalyzed with inverse-probability weights to create race-neutral GLI global (2022) equations. The inclusion of sitting height slightly improved the statistical precision of reference equations compared with using standing height alone but did not explain observed differences in spirometry between the NHANES III race and ethnic groups. GLI global (2022) equations, which do not require the selection of race and ethnicity, had a similar fit to the GLI 2012 "other" equations and wider limits of normal. The use of a single global spirometry equation reflects the wide range of lung function observed within and between populations. Given the inherent limitations of any reference equation, the use of GLI global equations to interpret spirometry requires careful consideration of an individual's symptoms and medical history when used to make clinical, employment, and insurance decisions.